The establishment of a molecular diagnostic platform for mitochondrial diseases: From conventional to next-generation sequencing - Ni-Chin Tsai; Chai-Wai Liou; Yin-Hua Cheng; Hao-Ting Lien; Tzu-Ling Lin; Tsu-Kung Lin; Min-Yu Lan; Pi-Lien Hung; Tzu-Jou Wang; Chen-Hao Lee; Yi-Chih Liang; Kuo-Chung Lan (Biomedical Journal)
Background: The aim of this study was to create a molecular diagnostic platform and establish a diagnostic pipeline for patients highly suspected of mitochondrial disorders. The effectiveness of three methods, namely, traditional restriction fragment length polymorphism-polymerase chain reaction (RFLP-PCR), Sanger sequencing for hotspot detection and whole mitochondrial DNA (mtDNA), and third-generation (Nanopore) whole mtDNA sequencing, will be compared in diagnosing patients with suspected primary mitochondrial diseases (PMDs). The strengths and limitations of different methods are also discussed. Material and methods: A single-center prospective cohort study was conducted to validate the diagnostic pipeline for suspected mitochondrial diseases. In the first stage, a PCR-based method with five sets of primers was used to screen for eight hotspots (m.3243A > G, m.3460G > A, m.8344A > G, m.8993T > G, m.9185T > C, m.11778G > A, m.13513G > A, and m.4977deletion) using either RFLP or direct Sanger sequencing. Sanger sequencing was also used to confirm the RFLP-positive samples. In the second stage, for samples with negative screening results for the eight hotspots, mitochondrial whole-genome sequencing was performed using Sanger sequencing or third-generation nanopore sequencing. Results: Between June 2020 and May 2023, 30 patients from ages 0 to 63 with clinically suspected mitochondrial disease were enrolled. The positive yield for the diagnosis of PMDs was 8/30 = 26.7%, and the sensitivity of the heteroplasmy level for the RFLP-based method was approximately 5%. The remaining 22 patients who tested negative at the first stage were tested using Sanger sequencing or the third-generation sequencing Nanopore, and all tested negative for pathological mtDNA mutations. Compared to the Sanger sequencing method, the results of RFLP-PCR were compromised by the limitations of incomplete RFLP enzyme digestion. For whole-genome sequencing of mtDNA, Sanger sequencing, instead of nanopore sequencing, is preferred at our institution because of its cost-effectiveness. Conclusions: In our highly selective cohort, most tested positive in the first stage of the 8 hot spots screen. Sanger sequencing is a conventional and accurate method for mitochondrial disease screening, at least for the most common hot spots in the region. The results revealed that Sanger sequencing is an accurate method with the benefit of being more cost-effective. This integral platform of molecular diagnosis bears the advantages of being relatively low cost and having a shorter reporting time, facilitating crucial identification of patients with clinical evidence of such disorders. This diagnostic flowchart has also been translated into routine clinical use in the tertiary hospital.